Women segregation in the labour market: the strength of the weak gender - Oliveira, L.; Carvalho, H. (8th Conference of the European Sociological Association: Conflict, Citizenship and Civil Society. Research Network: Sociology of families and intimate lives. European Sociological Association (ESA), 2007)
Taking as our starting point the idea of gender discrimination in labour market conditions, our main question in this paper is to discover to what extent this discrimination still exists and in which aspects it is most felt, after 50 years of social policies to improve gender equality . On the basis of Labour Force Survey statistics for 2005, we also analyse the main differences between 10 European countries – Belgium, Denmark, France, Germany, Greece, Ireland, Italy, Portugal, Spain and UK – in a search for common behaviour patterns. We begin by reflecting on the meaning of discrimination in relation to certain concepts and on measurement problems in labour market indicators, in general, and in gender discrimination, in particular.